ABANDONED TO DIFFERENCE: IDENTITY, OPPOSITION AND TRINH T. MINH-HA'S REASSEMBLAGE - Hill, Michael (Surfaces, 1993)
This essay is about the realization of power's proximity, and about how, once taken seriously, power forces us (1) to disband the outmoded notion of representing a generalized Other, and (2) abandon the Other's co-ordinate, subjective political agency. A tentative premise describes how the proximity of power — its stickiness — forces us to seek more politically informed notions about otherness and identity than could previously be thought. Upon that basis, an argument is built on behalf of a politics that attempts to exceed subjective agency by abandoning identity to politics, rather than abandoning politics to identity. Althusser, Foucault, West, Mudimbe, and Trin Minh-ha are brought into the discussion.